2022
DOI: 10.1007/s10534-021-00358-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterisation of phenanthroline-oxazine ligands and their Ag(I), Mn(II) and Cu(II) complexes and their evaluation as antibacterial agents

Abstract: A series of phenanthroline-oxazine ligands were formed by a cyclisation reaction between L-tyrosine amino acid esters and 1,10-phenanthroline-5,6-dione (phendione). The methyl derivative of the phenanthroline-oxazine ligand 1 was complexed with Ag(I), Mn(II) and Cu(II) to form [Ag(1) 2 ]ClO 4 , [Mn(1) 3 ](ClO 4 ) 2 and [Cu(1) 3 ](ClO 4 ) 2 . The activity of these metal complexes was tested against the bacteria Escherichia coli and Staphylococcus aureus. Each of the metal complexes was more active than 1 agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…It is well known that chelation is not the only criterion for antibacterial activity. Some important factors such as the nature of the metal ion, the nature of the ligand, the coordinating sites, the geometry of the complex, the concentration, hydrophilicity, lipophilicity, and the presence of co-ligands have a considerable influence on the antibacterial activity [ [34] , [35] , [36] ]. Complexes containing heterocyclic ligands have a more possibility of interacting with nucleoside ases [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that chelation is not the only criterion for antibacterial activity. Some important factors such as the nature of the metal ion, the nature of the ligand, the coordinating sites, the geometry of the complex, the concentration, hydrophilicity, lipophilicity, and the presence of co-ligands have a considerable influence on the antibacterial activity [ [34] , [35] , [36] ]. Complexes containing heterocyclic ligands have a more possibility of interacting with nucleoside ases [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…In previously reported literatures, the Bi-O bond distances are usually in the range from 2.064(7) to 3.455(2) Å. [37][38][39][40][41] Cu-O bond distances are in the range of 1.858 (19)…”
Section: Crystal Structurementioning
confidence: 99%
“…As pathogenic microorganisms may spread directly from one person to another or indirectly through surface contamination, developing new copper antibacterial drugs and their mechanism of action have been the focus of researchers. The mechanism of microbial death caused by copper is debatable, and the significance and contribution of each mechanism are unknown 19 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ag(I) and Cu(II) bis -complexes of 1 showed stronger binding to calf-thymus DNA than their phen analogues or the minor groove binding drugs, pentamidine and netropsin (McCann et al 2013 ). We previously carried out a study focused on the antibacterial ( Escherichia coli, Staphylococcus aureus and methicillin-resistant S. aureus (MRSA)) properties of Cu(II) complexes of 1 and a series of more lipophilic analogues (Ahmed et al 2022 ). These studies showed that the lipophilicity of the ligand did influence the antibacterial activity, with the complexes containing the hexyl and octyl alkyl chains showing the highest activity.…”
Section: Introductionmentioning
confidence: 99%